Apocatastasis of the Mind - Bonilla, Jason Andrey (2025)
The objective is to assess whether Kant, by grounding the Critique of Pure Reason in the principle of significance, that is, the principle according to which there is no legitimate use of concepts unless they are related to the empirical conditions of their application, returns to an Aristotelian position on the mind. To this end, the cognitive architecture of transcendental dialectic is analyzed, with particular attention to the paralogisms and the consequent dismantling of the Cartesian rational doctrine of the soul. The central question is to determine whether, by overcoming the split between rationalism and empiricism, critical philosophy leans toward idealism or realism. Adopting the second path, the development will be explicitly based on the key postulates of Peter Strawson's classic essay (1975) on the limits of meaning and implicitly on the theoretical framework of Konstantin Pollok's recent work (2017) on the space of normativity—both dedicated to Kant's work. After outlining the elements of the logic of illusion in dogmatic metaphysics, the paper concludes by refuting the hypothesis of an Aristotelian return, as for Kant, the mind is never a substance.